2012
DOI: 10.5194/nhess-12-1641-2012
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of flood risk change in residential areas

Abstract: Abstract. The observed increase of direct flood damage over the last decades may be caused by changes in the meteorological drivers of floods, or by changing land-use patterns and socio-economic developments. It is still widely unknown to which extent these factors will contribute to future flood risk changes.We survey the change of flood risk in terms of expected annual damage for residential buildings in the lower part of the Mulde River basin (Vereinigte Mulde) between 1990 and 2020 in 10-yr time steps base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 43 publications
0
76
0
1
Order By: Relevance
“…However, the relative contributions of both factors are similar. Elmer et al (2012) obtained opposite results in a German catchment. Based on the study of the drivers of flood risk change in residential areas between 1990 and 2020, they concluded that the expansion of residential areas would be the main driver of flood risk evolution in this region.…”
Section: Relative Contribution Of Climate Change and Urbanizationmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the relative contributions of both factors are similar. Elmer et al (2012) obtained opposite results in a German catchment. Based on the study of the drivers of flood risk change in residential areas between 1990 and 2020, they concluded that the expansion of residential areas would be the main driver of flood risk evolution in this region.…”
Section: Relative Contribution Of Climate Change and Urbanizationmentioning
confidence: 89%
“…First, the wet climate scenario considered here is relatively extreme, and the time horizon (2100) is more distant than those used in the two previous studies. As emphasized by Elmer et al (2012), the climate influence could be more decisive in the long term. Second, the land use characteristics of the three studied areas are very different: the study area in the present study is much more urbanized than those analysed by Elmer et al (2012) and Poussin et al (2012).…”
Section: Relative Contribution Of Climate Change and Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase can be attributed to socio-economic factors, including settlement growth near rivers and the rise in the concentration of values in these areas (Evans et al 2004;Barredo 2009;Munich Re 2013), which has been confirmed in numerous empirical analyses. A German study of a Mulde sub-catchment, for instance, showed that land-use change in the form of urban sprawl is a key driver of flood risk (Elmer et al 2012). Similarly, a study on the development of flood exposure in the Netherlands found that socio-economic change and the increase in urban area in flood-prone zones have led to an exponential increase in potential flood damage during the twentieth century (de Moel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the occurrence probability and intensity of certain extreme weather events is highly uncertain, they appear with serious damage potential or health risks [4]. Beyond others increased surface runoff due to surface sealing in urban areas leads to massive inundation and damage [5]. Urbanized areas have historically often developed close to rivers and are thus located in flood prone areas and affected by floods.…”
Section: Introductionmentioning
confidence: 99%